2016
DOI: 10.1002/jcu.22339
|View full text |Cite
|
Sign up to set email alerts
|

Internal jugular vein/common carotid artery cross‐sectional area ratio and central venous pressure

Abstract: Assessing the IJV/CCA ratio with a portable sonographic device could be a noninvasive alternative for central venous catheterization in order to evaluate the hemodynamic status of critically ill patients. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 44:312-318, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 21 publications
(46 reference statements)
1
17
2
Order By: Relevance
“…Another innovative ultrasound technique based on the IJV/common carotid artery cross‐sectional ratio has been recently described as an alternative for central venous catheterization in ICU. The comparison of the 2 sonographic techniques would be very interesting.…”
Section: Discussionmentioning
confidence: 99%
“…Another innovative ultrasound technique based on the IJV/common carotid artery cross‐sectional ratio has been recently described as an alternative for central venous catheterization in ICU. The comparison of the 2 sonographic techniques would be very interesting.…”
Section: Discussionmentioning
confidence: 99%
“…Najed et al reported a significant positive correlation between the CVP and IJV/CCA ratio (r = 0.734, p < 0.05). Sensitivity, specificity, and the positive and negative predictive value of the IJV/CCA diameter ratio for CVP estimation were 90%, 86.36%, 90%, and 86.36%, respectively [6]. Hilbert et al reported that the IJV/CCA ratio using ultrasound is an effective non-invasive alternative for CVP measurement among critically ill patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, overlap of the common carotid artery and internal jugular vein is more in pediatrics. A larger diameter ratio of the internal jugular vein to common carotid artery may partially explain this result: in adults, it is 1.90±0.83 vs 1.84±0.41 in our study (data not shown). We also found that overlap of the common carotid artery and internal jugular vein decreases, and the common carotid artery moved medially relative to the internal jugular vein from the cricoid cartilage level to the supraclavicular level.…”
Section: Discussionmentioning
confidence: 44%